The Results of Developmental Task Inventory(ITP) For Guidance and Counseling Services at Islamic Boarding Schools - Kusaini, Utami Niki (Universitas Mercu Buana Yogyakarta, 2021)
Guidance and counseling service is useful for students in Islamic Boarding Schools but to determine service based on the requirement of students is difficult. This research purposed to describe the results ofDevelopmental Task Inventory(ITP) to help students find developmental tasks that have not been achieved. This research used survey method. The respondents of this research six classes with the amount of 445 students in two Boarding School of Yogyakarta. The results showed that the achievement of development tasks students above the average growth rate of 3.75. The task of development is not yet achieved (<3.75). Based on these results, the researcher sees each class having differences in aspects of development tasks that have not been achievedand require different guidance and counseling services.